1998
DOI: 10.1097/00001756-199810050-00018
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones modulate response patterns of human brain activity

Abstract: Mobile phones emit a pulsed high-frequency electromagnetic field (PEMF) which may penetrate the scalp and the skull. Increasingly, there is an interest in the interaction of this pulsed microwave radiation with the human brain. Our investigations show that these electromagnetic fields alter distinct aspects of the brain's electrical response to acoustic stimuli. More precisely, our results demonstrate that aspects of the induced but not the evoked brain activity during PEMF exposure can be different from those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 7 publications
5
67
2
1
Order By: Relevance
“…Several studies have investigated the interaction between mobile phones and brain functions in humans including their effect on hearing [9][10][11][12][13][14][15][16][17]. Some of the similar recent studies have been highlighted below:…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the interaction between mobile phones and brain functions in humans including their effect on hearing [9][10][11][12][13][14][15][16][17]. Some of the similar recent studies have been highlighted below:…”
Section: Discussionmentioning
confidence: 99%
“…Eulitz et al reported a modulation in the high-frequency bands of the EEG after task-relevant but not after standard auditory stimuli [26]. Freude et al found an effect on preparatory slow brain potentials for visual monitoring tasks, but not for less demanding tasks such as finger movements [31,32].…”
Section: Changes In Eeg-and Sleep-parametersmentioning
confidence: 99%
“…Eulitz et al [1998] studied the interaction of cell phone pulsed MW exposure within the human brain. Subjects were 13 healthy males 21-27 years old.…”
Section: Electroencephalography and Evoked Responsesmentioning
confidence: 99%